Antibiotic Susceptibility of Isolates from Blood of Patients in Intensive Care Units of Emergency Medical Service - T. V. Chernenkaya; L. A. Borisova; T. YU. Vorobyeva; I. V. Aleksandrova; D. A. Kosolapov (Антибиотики и Химиотерапия, 2020)
The microbiological tests of 769 blood samples from 220 patients, treated in 4 intensive care units of the N.V. Sklifosovsky Research Institute for Emergency Medical Service within a period from January 2009 to June 2010, were analysed. Etiologically significant microorganisms were detected in 323 samples (42%). 253 isolates were used in the analysis. Grampositive and gramnegative pathogens were detected in 47 and 42% of the cases respectively. Candida and anaerobic organisms were isolated in 8 and 3% of the cases respectively. Staphylococcus aureus and enterococci were isolated in 24 and 15% of the cases respectively. Nonfermenting gramnegative bacteria and enterobacteria were revealed in 25 and 17% of the cases respectively. Differences in the spectrum of the sepsis pathogens depending on the patients contingent were shown. The maximum summary susceptibility of the grampositive cocci was observed with respect to vancomycin and linezolid and that of the gramnegative bacteria was stated with respect to imipenem and meropenem.